Doskonalenie zarządzania jakością w przedsiębiorstwie przemysłowym - Gazda, Andrzej (Improvement of Quality Management in Industrial Enterprise, 2006)
The functioning of an enterprise and its existence and development depends on an endless improvement of its management system. There are different ways and methods of achieving the level of an excellent organisation. The example of the efficient achievement of such a level is the Achieving Competitive Excellence system.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1116, s. 253-259